Effectiveness of State Science and Technology Policy in USSR at Turn of 1960s and 1970s - E. V. Bodrova; V. V. Kalinov; V. N. Krasivskaya (Научный диалог, 2025)
This study examines the evolution of the state science and technology policy in the USSR at the turn of the 1960s and 1970s, utilizing declassified archival documents to assess its effectiveness across several key areas. The findings demonstrate that the analyzed documents provide substantial evidence that central party-state organs — thanks to the efforts of the State Planning Committee of the USSR, the Academy of Sciences of the USSR, and the State Committee for Science and Technology under the Council of Ministers — obtained concrete information regarding both the overall scientific and technological potential of the country and specific sectors. It is reported that comparative metrics with the United States and other leading capitalist nations were traditionally included in such reports, serving as arguments that drew leadership attention to various issues while corroborating the authors’ conclusions. The study identifies several critical blocking factors, including insufficient funding, low investment efficiency, prolonged construction projects, subpar quality of domestic equipment, and a lack of competence among certain high-ranking government officials, as well as the neglect of recommendations from leading scientists; a departmental approach, inadequate collaboration between civilian and defense sectors of science, and a shortage of specialists in key areas. Furthermore, it is noted that trends in the development of the scientific and technological sphere in leading countries indicated the emergence of national innovation systems that have proven effective.